Worldviews in Bioethics: interpretation of pain and suffering - Cerdio-Domínguez, David (2023)
Problem statement: Pain is an integral part of the human experience. Therefore, it is important to analyze from Bioethics and its currents of thought the approach to this reality. Objectives: Analyze the phenomenon of pain and suffering based on the different worldviews of Bioethical thought. Materials and Methods: A bibliographic search was carried out from August 2021 to March 2022 using the following search engines: PubMed, EBSCO Host, Web of Science and Scielo. As inclusion criteria: articles that presented a bioethical analysis related to pain management were chosen. As exclusion criteria, all those articles that presented aspects related to pain management or bioethical analysis in an unrelated manner were discarded. Results: The interpretation of pain and its meaning from the different worldviews: liberalism, sociobiologism, utilitarianism and bioethical personalism is crucial, since it manifests a convergent problem, and allows a comprehensive approach to aspects of life experience. Pain and suffering are realities that often confront the person in search of their meaning in life. Conclusions: The differences between the currents of thought highlight how each of these worldviews seeks to understand how the person benefits. It is the duty of Bioethics to establish a field of dialogue, thus allowing a unified construction of society where the pertinent methodologies are systematically established to defend and promote the value of the human person.